Pengembangan produk pertanian organik berbasis sumber daya lokal untuk meningkatkan pendapatan keluarga - Agus Syam; Syamsul Sunusi; Andi Agussalim A.J. (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
The aim of this program was (1) to increase theknowledge and skills of the target group in order to manage 3Twaste into compost and liquid organic fertilizer; (2) tointroduce the appropriate technology for the composter for thecommunity as a tool for the composting process; (3) to provideknowledge and skills of the targeted group community to beable to meet the family's nutritional needs through themanagement of the yard as a food (vegetable) home; (4) toprovide business management skills, production, marketingand packaging of fertilizer products. The results of theimplementation of learning and community empowermentprogram showed: (1) the number of participants who activelyparticipated in this learning and empowerment program was45 people who were Raskin recipients; (2) training participantshave had the knowledge and skills in making hydroponics,liquid organic fertilizer (POC), and composting; (3) threehydroponic model houses were built in Bilokka, Corawali, andLise Villages, respectively. It is recommended that the LocalGovernment learn and empower the community through thedevelopment of organic resources based on local resources toincrease family income. Thus, an intense assistance can beconducted in order to improve the living standards of thecommunity.